THE ASSESSMENT OF THE IMPACT OF MONETARY POLICY ON ECONOMIC GROWTH IN DIFFERENT GROUPS OF COUNTRIES - F. S. Kartaev (Финансы: теория и практика, 2018)
Topic. This paper analyzes the impact on the growth of a selection of different targets of monetary and credit policy: the discretionary policy; targeting the money supply; inflation targeting; and fixed exchange rate regime.Purpose. We tried to identify the optimal (from the point of view of stimulating the long-term economic growth) regime of monetary and credit policy. Methodology. We used panel data for 188 countries for the period between 1999 and 2015. Using models with fixed effects there were estimated long-run dynamic multipliers of the policy regimes of the Central Bank. The advantage of the presented work in comparison with previous studies is that, first, in the same model simultaneously we compare all the main targets of monetary policy, and, secondly, there was investigated a number of specific subsamples of countries formed with different criteria, such as belonging to a particular continent, the nature of the economy, and the level of ethnolinguistic diversity. Regression analysis is complemented by discussion of specific examples of the change target policy by the monetary authorities of countries belonging to different subsamples under consideration.Results. In the course of econometric modeling, we revealed a consistent (for a group of countries under consideration) the positive impact of inflation targeting on long-term dynamics of the outcome. For alternative nominal anchors for monetary policy of such a sustainable eff ect was not revealed. Conclusions. Mere or mixed modes of inflation targeting can be recommended to the Central banks of both developed and developing countries if, in addition to achieving price stability, one of their long-term goals is to create conditions for economic growth.